Severe and Enduring' Stage in Anorexia Nervosa: Comparing Eating Attitudes, Impairment and Associated Psychopathology - Ramos, Rita; Vaz, Ana; Rodrigues, Tânia F.; Pinto-Bastos, Ana; Brandão, Isabel; Neves, António; Conceição, Eva; Machado, Paulo P. P. (Frontiers in Nutrition, 2022)
This study aimed to assess differences in eating attitudes, impairment, and related psychopathology at treatment presentation for patients with “non-severe and enduring Anorexia Nervosa” (illness duration of less than 7 years) and patients with “severe and enduring Anorexia Nervosa” (illness duration of 7 years or more). One hundred and thirty-nine patients diagnosed with Anorexia Nervosa participated in this study. Participants were interviewed with the Eating Disorder Examination (EDE) and asked to complete several questionnaires at the end of the first treatment appointment. We also explored differences at treatment presentation by considering alternative criteria to define groups, namely a composite of illness duration and clinical impairment (≥16 CIA total score). No differences were found when comparing participants based on illness duration. However, when participants were classified into a different classification scheme: “non-severe and enduring Anorexia Nervosa” (illness duration <7 years and a CIA total score <16) versus “severe and enduring Anorexia Nervosa” (illness duration ≥7 years and CIA total score ≥16), significant differences were found in terms of eating pathology, depressive symptomatology, psychological distress, and emotion dysregulation. Further research is needed to better understand the role of illness duration and clinical impairment in informing the course of AN.